Prevalence of biofilm controlling ica genes of Staphylococcus epidermidis detected in healthy skin, blood samples from septicaemia patients and chronic wounds - Hussain, Malik Asif; Rathnayake, Irani Udeshika; Huygens, Flavia (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The role of microbes in the persistence of chronic wounds is very important. Biofilm mode of bacterial growth has been found to be clinically very important in various types of infections. Bacterial growth in the form of biofilm is now being considered as a strong and effective mechanism of bacterial survival and growth in chronic wounds. Therefore it is clinically important to further investigate and determine the bacterial groups involved in the formation of biofilm in wounds and their mechanism of interference with the normal healing process. Methods: This study focussed on determining the presence of S. epidermidis ica genes, which are responsible for biofilm production by this species. We investigated the presence of these genes in skin, blood and wound samples. In total, 296 samples were tested for the presence of the ica genes. RT-PCR and conventional PCR testing was performed on these samples from different sources. Results: Our results show that there is presence of a significant number of ica positive samples both in skin and blood specimens while only a very small percentage of ica positive samples present in chronic non-healing wound samples. Conclusions: Presence of ica genes in blood samples indicate involvement of ica positive S. epidermidis in the case of blood infection. In chronic wound samples, there is a small percentage of samples positive for these genes thus biofilm producing bacteria other than S. epidermidis are likely to be more important in the case of chronic wounds.